Best practices for Core Argo floats - Part 2: physical handling, deployment and metadata considerations - Tamaryn Morris; Megan Scanderbeg; Deborah West-Mack; Claire Gourcuff; Noé Poffa; Tata V. S. Udaya Bhaskar; Craig Hanstein; Steve Diggs; Lynne Talley; Victor Turpin; Zenghong Liu; Breck Owens (Frontiers in Marine Science, 2024)
Following on from Part 1: Best Practices for Core Argo floats - Getting started and data considerations, we present Part 2: Best Practices for Core Argo floats in terms of physical handling and deployments and recommended metadata parameters. The objective is to encourage new and developing scientists, research teams and institutions to contribute to the OneArgo Program through increased deployments regionally, specifically to the Core Argo mission. Only by leveraging sustained contributions of current Core Argo float groups with new and emerging Argo teams and users, can the OneArgo initiative be realized. This paper makes involvement with the Core Argo mission smoother by providing a framework endorsed by a wide community for these observations.

Best practices for Core Argo floats - part 1: getting started and data considerations - Tamaryn Morris; Megan Scanderbeg; Deborah West-Mack; Claire Gourcuff; Noé Poffa; T. V. S. Udaya Bhaskar; Craig Hanstein; Steve Diggs; Lynne Talley; Victor Turpin; Zenghong Liu; Breck Owens (Frontiers in Marine Science, 2024)
Argo floats have been deployed in the global ocean for over 20 years. The Core mission of the Argo program (Core Argo) has contributed well over 2 million profiles of salinity and temperature of the upper 2000 m of the water column for a variety of operational and scientific applications. Core Argo floats have evolved such that the program currently consists of more than eight types of Core Argo float, some of which belong to second or third generation developments, three unique satellite communication systems (Argos, Iridium and Beidou) and two types of Conductivity, Temperature and Depth (CTD) sensor systems (Seabird and RBR). This, together with a well-established data management system, delayed mode data quality control, FAIR and open data access, make the program a very successful ocean observing network. Here we present Part 1 of the Best Practices for Core Argo floats in terms of how users can get started in the program, recommended metadata parameters and the data management system. The objective is to encourage new and developing scientists, research teams and institutions to contribute to the OneArgo Program, specifically to the Core Argo mission. Only by leveraging sustained contributions from current Core Argo float groups with new and emerging Argo teams and users who are eager to get involved and are actively encouraged to do so, can the OneArgo initiative be realized. This paper presents a list of best practices to get started in the program, set up the recommended metadata, implement the data management system with the aim to encourage new scientists, countries and research teams to contribute to the OneArgo Program.

XBT operational best practices for quality assurance - Justine Parks; Francis Bringas; Rebecca Cowley; Craig Hanstein; Lisa Krummel; Janet Sprintall; Lijing Cheng; Mauro Cirano; Samantha Cruz; Marlos Goes; Shoichi Kizu; Franco Reseghetti (Frontiers in Marine Science, 2022)
Since the 1970s, eXpendable BathyThermographs (XBTs) have provided the simplest and most cost-efficient solution for rapid sampling of temperature vs. depth profiles of the upper part of the ocean along ship transects. This manual, compiled by the Ship of Opportunity Program Implementation Panel (SOOPIP) a subgroup of the Global Ocean Observing System (GOOS) Observations Coordination Group (OCG) Ship Observations Team (SOT) together with members of the XBT Science Team, aims to improve the quality assurance of XBT data by establishing best practices for field measurements and promoting their adoption by the global operational and scientific community. The measurement system components include commercially available expendable temperature probes, the launcher, the data acquisition (DAQ) hardware, a Global Navigation Satellite System (GNSS) receiver, an optional satellite transmitter, and a computer with software controls. The measurement platform can be any sea-going vessel with available space for the equipment and operator, and capable of oceanic voyages across the regions of interest. Adoption of a standard methodology in the installation and deployment of the measurement system will lead to data quality improvements with subsequent impact on the computation and understanding of changes in the near surface ocean properties (e.g., heat content), ocean circulation dynamics, and their relationship to climate variability.

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)